PESANTREN DAN PENGEMBANGAN ILMU KEISLAMAN: Studi Kasus Pembelajaran Fiqh di Pondok Pesantren Salafiyah Syafi'iyah Sukorejo Situbondo - M. Hasan Basri (LP2M Universitas Ibrahimy, 2013)
Islamic boarding school is an institution of al-tafaqquh fi al-din, the educational institution that focuses on the development of religious sciences, especially the Islamic jurisprudence. In the structure of religion, the Islamic jurisprudence occupies a central position and even the most concrete appearance of Islam due to direct contact with the various provisions of the law in daily religious life and society. The development of the science of jurisprudence continues in Pondok pesantren as reflected in the establishmentÂ of Ma'had Aly at Islamic boarding school of Salafi Syafi'iyah Situbondo. As a typical boarding institutions of higher education, Ma'had Aly Situbondo, as an institution of high education in pesantren-style, is projected to be the center ofÂ Islamic jurisprudence development (fiqh center) in response to a variety of legal issues among society. The fiqh development in Ma'had Aly Situbondo has a different perspective from the boarding schools in general because of placing usul fiqh as a method of istinbatal al-hukm on a very central position in the fiqh study and the formulation of the laws applied.Â